Le fratture articolari ed extra-articolari del ginocchio - Rocca, G.; Colasanto, G.; De Venuto, A.; De Sal, A. (Lo Scalpello - Journal, 2018)
ARTICULAR AND EXTRA-ARTICULAR KNEE FRACTURES Joint fractures of the knee include epiphyseal detachments of the distal femur and proximal tibia (types 3 and 4 according to Salter-Harris). Extra-articular fractures include: avulsion of the tibial spines, detachment of the anterior tuberosity and patellar fractures. Fractures involving the distal femoral and proximal tibial epiphysis are relatively infrequent but may lead to long-term complications owing to the formation of post-traumatic bone bridges. Unless the fracture is composed, surgical treatment is always indicated. Avulsion fractures of the tibial spines occur as a result of a chondro-epiphyseal detachment of the insertion of the cruciate ligaments (predominantly the anterior one). They are infrequent injuries (3 per 100,000 cases per year, 2% of all knee injuries). Accurate diagnosis and appropriate treatment prevent unfortunate outcomes. Adolescent tibial tubercle fractures are uncommon, high-energy injuries sometimes combined with patellar tendon rupture; they represent a frequently missed diagnosis. Open reduction/internal fixation is generally required. Patellar fractures are caused by direct trauma (primary osseous fractures) or by an eccentric load during extension of the knee (sleeve and avulsion fractures). Most fractures require open reduction/internal fixation. The complication rate is low but late reconstruction of missed injuries may result in an extensor deficit.